INDEKS PENILAIAN KEAMANAN INFORMASI UNTUK MENGUKUR KEMATANGAN MANAJEMAN KEAMANAN LAYANAN TI (Studi Kasus BPMP Kabupaten Gresik) - Rahmat Hidayat; Mohammad Suyanto; Andi Sunyoto (Universitas Janabadra, 2018)
This study contains the results of measurement of the maturity of Information Security Management System (ISMS) in the Gresik District The result of measurement of the completeness and maturity of the ISMS in BPMP Gresik Regency is still relatively low, that is at the level of I to II which means the maturity level is stated in the initial condition up to the implementation of the basic framework, it is still under standard ISO 27001: 2009. And for the evaluation of the level of completeness of the implementation of the five areas with the achievement score of 207, then according to the Indeks KAMI mean readiness status is considered